Identidad nacional, historia e invención de tradiciones en El Salvador en la década de 1920 - López Bernal, Carlos Gregorio (Revista de historia., 2002)
The author studies the process which led to the elevations of Atlacatl, the indigenous chieftain who lead the resistance of the inhabitants of Cuscatlán against the spanish invaders, to the status of national hero towards the end of the 1920s.